Method for producing rare earth magnetic powder, magnetic particles, and rare earth magnets
Patent Information
- Application Number
- JP2025060071
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0016】 以上の態様によれば、磁気特性が良好な希土類磁石の材料となる希土類磁性粉末及び磁性粒子を提供することができ、磁気特性が良好な希土類磁石を製造する希土類磁石の製造方法を提供することができる。
Smart Images

Figure 2026166853000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a rare earth magnetic powder that is a material for rare earth magnets, magnetic particles that are a material for rare earth magnets, and a method for manufacturing a rare earth magnet for producing a rare earth magnet.
BACKGROUND ART
[0002] In recent years, initiatives toward realizing a low-carbon society or a decarbonized society have become active, and research and development on electrification technologies have been conducted for vehicles as well, in order to reduce CO₂ emissions and improve energy efficiency. One of the methods for improving energy efficiency is to improve the efficiency of motors used as power sources. In order to improve motor efficiency, rare earth magnets have been widely used in recent years. And it is required to improve the magnetic properties of rare earth magnets. Since rare earth magnets are metallic magnets with low electrical resistivity, they have the problem that eddy current loss tends to increase. Accordingly, there are techniques for reducing overcurrent loss in rare earth magnets.
[0003] Patent Document 1 discloses a rare earth magnet capable of reducing eddy current loss, which has rare earth magnet powder covered with a film-like coating layer containing a rare earth oxide. Between the particles of the magnet powder in the state coated with the rare earth oxide, a binding portion containing particles of the rare earth oxide is interposed. The rare earth magnet is manufactured by subjecting a mixture of the rare earth magnet powder coated with the rare earth oxide and the rare earth oxide to high-temperature pressure molding.
[0004] Patent Document 2 discloses a method for manufacturing a rare earth magnet, in which for the purpose of increasing the electrical resistivity of the rare earth magnet, magnet powder made of an alloy mainly composed of an Nd₂Fe₁₄B compound is mixed with one or two or more insulating compounds selected from oxides such as CaO, nitrides such as BN, or fluorides such as CaF₂, and this mixture is subjected to hot plastic working to obtain an anisotropic magnet material.
[0005] Patent Document 3 discloses a first method for manufacturing rare earth magnets, comprising the steps of: preparing isotropic quenched powder such as Nd-Fe-B magnet powder; mixing the isotropic quenched powder with a predetermined compound that will form an insulating layer; cold forming (pre-forming) the mixture; hot forming (densifying) the cold-formed body; and hot plastic working (anisotropizing). It is stated that the magnets manufactured by this method have a structure in which Nd-Fe-B quenched powder with a long side of 100 to 400 μm and a thickness of 20 to 40 μm is generally stacked on top of each other via compound powder. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Patent No. 4784173 [Patent Document 2] Japanese Patent Publication No. 2003-22905 [Patent Document 2] Japanese Patent Publication No. 2010-27852 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] The rare earth magnet described in Patent Document 1 uses an insulator made of dysprosium oxide (Dy2O3) as the rare earth oxide. Since dysprosium oxide is hygroscopic, the magnetic properties of the rare earth magnet may be reduced by water adsorbed on the dysprosium oxide. In the method for manufacturing a rare earth magnet described in Patent Document 2, in the mixing step in which Nd-Fe-B magnet powder and an insulating compound are mixed, the magnet powder is pulverized and excessively subdivided, increasing the specific surface area of the magnet powder and making it more susceptible to oxidation. As a result, the rare earth magnet may be oxidized, which may reduce the magnetic flux density of the rare earth magnet.
[0008] In the rare earth magnet manufacturing method described in Patent Document 3, compound A, which is at least one selected from the group consisting of fluorides, oxides, and inorganic salts of heavy rare earth elements, and compound B, which is a hydride of an alkaline earth metal, are reacted during the hot forming and heat treatment processes. However, side reactions such as oxidation of the magnet or improper reaction between compound A and compound B may reduce the magnetic properties of the manufactured rare earth magnet. Therefore, there is a need for rare earth magnet materials with good magnetic properties and for rare earth magnets with good magnetic properties.
[0009] In view of the above background, the present invention aims to provide rare earth magnetic powder and magnetic particles that can be used as materials for rare earth magnets with good magnetic properties such as residual magnetic flux density, and to provide a method for manufacturing rare earth magnets that produce rare earth magnets 1 with good magnetic properties such as residual magnetic flux density, thereby contributing to the improvement of energy efficiency. [Means for solving the problem]
[0010] To solve the above problems, one aspect of the present invention is a rare earth magnetic powder, which is a material for a rare earth magnet, and is in the form of flakes with a particle size of 500 μm or more and 600 μm or less.
[0011] According to this embodiment, it is possible to provide a rare earth magnetic powder that can be used as a material for rare earth magnets with good magnetic properties.
[0012] To solve the above problems, one aspect of the present invention provides magnetic particles that are a material for a rare earth magnet, comprising a flaky rare earth magnetic powder and an insulating layer having insulating properties formed on the surface of the rare earth magnetic powder, wherein the particle size of the rare earth magnetic powder is 500 μm or more and 600 μm or less.
[0013] According to this embodiment, magnetic particles that can be used as materials for rare-earth magnets with good magnetic properties can be provided.
[0014] To solve the above problem, one aspect of the present invention is a method for manufacturing a rare-earth magnet that produces a rare-earth magnet, the method including: an insulating layer forming step of forming an insulating layer having insulating properties on the surface layer of flaky rare-earth magnetic powder with a particle size of 500 μm or more and 600 μm or less to obtain the magnetic particles; a primary forming step of subjecting a plurality of the magnetic particles obtained in the insulating layer forming step to primary forming using a hot press to obtain a primary formed body in which the plurality of magnetic particles are primarily formed; and a hot plastic working step of performing hot plastic working on the primary formed body obtained in the primary forming step to obtain the rare-earth magnet.
[0015] According to this aspect, a rare-earth magnet with excellent magnetic properties can be manufactured. [Advantageous Effects of Invention]
[0016] According to the above aspects, it is possible to provide a rare-earth magnetic powder and magnetic particles that serve as materials for a rare-earth magnet with excellent magnetic properties, and to provide a method for manufacturing a rare-earth magnet that produces a rare-earth magnet with excellent magnetic properties. [Brief Description of Drawings]
[0017] [Figure 1] Schematic cross-sectional view of the rare-earth magnet according to the embodiment [Figure 2] Schematic cross-sectional view of the magnetic powder according to the embodiment [Figure 3] Diagram showing the method for manufacturing a rare-earth magnet according to the embodiment [Figure 4] Schematic diagram of a tumbling flow apparatus [Figure 5] Graph showing differences in residual magnetic flux density and coercivity between the rare-earth magnet manufactured from the rare-earth magnetic powder of the example and the rare-earth magnet manufactured from the rare-earth magnetic powder of the comparative example [Mode for Carrying Out the Invention]
[0018] Hereinafter, the rare-earth magnet 1 according to the embodiment of the present invention will be described in detail with reference to the drawings. In the following description, the expression "XX to XX" indicating a numerical range means "XX or more and XX or less" unless otherwise explicitly specified.
[0019] <Structure of Rare-Earth Magnet 1> FIG. 1 is a schematic cross-sectional view of the rare-earth magnet 1 according to the embodiment. As shown in FIG. 1, the rare-earth magnet 1 includes a plurality of rare-earth magnet powders 2 arranged in layers, and an insulating layer 3 formed on the surface layer of the rare-earth magnet powder 2 and having insulating properties. The insulating layer 3 covers the outer peripheral surface of the rare-earth magnet powder 2.
[0020] The rare-earth magnet powder 2 is preferably a flaky (flake-shaped) neodymium magnet (Nd-Fe-B based magnet, specifically Nd2Fe 14 B).
[0021] The insulating layer 3 includes a plurality of fluoride nanoparticles 3A composed of a fluoride. The fluoride nanoparticles 3A are particles composed of calcium fluoride (CaF2). Calcium fluoride (CaF2) has a melting point higher than that of the rare-earth magnet powder 2, and has low reactivity with the rare-earth magnet powder 2. The particle diameter of the fluoride nanoparticles 3A is preferably 1 to 100 nm.
[0022] The fluoride nanoparticles 3A may be any particles as long as they are composed of an insulating inorganic fluorine compound. The fluoride nanoparticles 3A preferably have a melting point higher than that of the rare-earth magnet powder 2 and low reactivity with the rare-earth magnet powder 2. Since the melting point is higher than the melting point of the rare-earth magnet powder 2 and the reactivity with the rare-earth magnet powder 2 is low, the fluoride nanoparticles 3A are preferably nanoparticles composed of alkali metal fluorides such as lithium fluoride, or nanoparticles composed of alkaline earth metal fluorides such as magnesium fluoride, barium fluoride, and strontium fluoride. The insulating layer 3 may include, as the fluoride nanoparticles 3A, a plurality of nanoparticles composed of an alkali metal fluoride and a plurality of nanoparticles composed of an alkaline earth metal fluoride. Further, the insulating layer 3 may include, as the fluoride nanoparticles 3A, nanoparticles containing an alkali metal fluoride and an alkaline earth metal fluoride.
[0023] As described later, during the manufacturing process of the rare earth magnet 1 (Hot plastic deformation process (E) in Figure 3), the rare earth magnet powder 2 is heated while being pressurized in a direction perpendicular to the main surface (first direction). As a result, the crystal grains in the magnet are shorter in the first direction (compression direction) and longer in the orthogonal direction perpendicular to the first direction (direction in which the main surface extends). In addition, the rare earth magnet 1 is magnetized in the first direction (compression direction). The orientation of the crystal grains of the rare earth magnet 1 as described above, and the magnetization as described above, increases the squareness ratio of the rare earth magnet 1.
[0024] <Structure of magnetic particle 6> Figure 2 is a schematic cross-sectional view of the magnetic particles 6 of the embodiment. The magnetic particles 6 are the material for the rare earth magnet 1. As shown in Figure 2, the magnetic particles 6 are a powder having a rare earth magnetic powder 7 and an insulating layer 8 that has insulating properties provided on the surface of the rare earth magnetic powder 7.
[0025] The composition of rare earth magnetic powder 7 is the same as that of rare earth magnet powder 2. Rare earth magnetic powder 7 is a flaky rare earth magnet. The particle size of rare earth magnetic powder 7 is between 500 μm and 600 μm. The average thickness of rare earth magnetic powder 7 is between 10 μm and 30 μm. Rare earth magnetic powder 7 is a flaky neodymium magnet (Nd-Fe-B type magnet, more precisely Nd2Fe 14 B) is preferable. The rare earth magnetic powder 7 is anisotropic, but may also be isotropic. Anisotropy is the property that the crystal orientations (easy magnetization axis, c-axis) are aligned in a specific direction. Isotropy is the property that the crystal orientations are not aligned in a specific direction.
[0026] The insulating layer 8 is provided on the surface of the magnetic particles 6 and covers the rare earth magnetic powder 7. The insulating layer 8 contains a binder compound and a plurality of fluoride nanoparticles 3A. As described above, the fluoride nanoparticles 3A are particles made of calcium fluoride (CaF2). The binder compound is an acrylic polymer with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer is thermally decomposable, decomposing at a temperature lower than the melting point of the rare earth magnetic powder 7.
[0027] The binder compound only needs to be able to bind the fluoride nanoparticles 3A. The binder compound has a weight-average molecular weight greater than 100,000, but it does not need to be less than or equal to 300,000. Also, the binder compound does not have to be an acrylic polymer. The binder compound should preferably be a resin.
[0028] <Method for manufacturing rare earth magnet 1> Figure 3 is a diagram showing a method for manufacturing a rare earth magnet 1. As shown in Figure 3, the method for manufacturing a rare earth magnet 1 includes (A) a magnetic powder manufacturing step for manufacturing rare earth magnetic powder 7, (B) an insulating layer formation step for forming an insulating layer 8 on the rare earth magnetic powder 7 to obtain magnetic particles 6, (C) a binder removal step for removing binder compounds contained in the magnetic particles 6 by thermal decomposition to obtain degreased magnetic powder 11, (D) a primary molding step for obtaining a primary molded body 12 by primary molding of the degreased magnetic powder 11 using a hot press, and (E) a hot plastic deformation step for obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 12.
[0029] (A) The magnetic powder manufacturing process is a process for manufacturing rare earth magnetic powder 7 in the form of flakes of a predetermined size. (A) The melt spinning method is preferably used in the magnetic powder manufacturing process. As shown in Figure 3(A), the melt spinning method is a method for obtaining thin plate-shaped magnets by spraying rare earth magnets, which have been heated to a liquid state, onto a roll and then cooling it. The composition of the rare earth magnets to be liquefied is the same as the composition of the rare earth magnet powder 2. Furthermore, the thin plate-shaped magnets are crushed to obtain minute magnet fragments 13. Then, the rare earth magnetic powder 7 is classified from the minute magnet fragments 13 to obtain the rare earth magnetic powder 7. Note that the melt spinning method is not required in the magnetic powder manufacturing process. (A) The magnetic powder manufacturing process may also be a process for obtaining rare earth magnetic powder 7 by crushing thin plate-shaped rare earth magnets.
[0030] The particle size of the rare earth magnetic powder 7 is between 500 μm and 600 μm. The average thickness of the rare earth magnetic powder 7 is between 10 μm and 30 μm. The rare earth magnetic powder 7 is anisotropic, but may also be isotropic. The oxygen concentration of the rare earth magnetic powder 7 is adjusted so that the rare earth magnet 1 obtained in the (E) hot plastic deformation process contains 0.12 wt% or less of oxygen.
[0031] The rare earth magnetic powder 7 is flaky and has a pair of main surfaces 7A. The main surface 7A is the largest of a pair of flat surfaces facing opposite directions. The rare earth magnetic powder 7 may have an aspect ratio of approximately 1 (for example, 0.7 to 1.0) when viewed from a direction perpendicular to the main surface 7A. The aspect ratio is the size of the minor axis b (minor axis diameter) relative to the major axis a (major axis diameter) of the particle (aspect ratio = minor axis b / major axis a). Here, the major axis a (major axis diameter) means the maximum Ferret diameter, and the minor axis b (minor axis diameter) means the minimum Ferret diameter. The measurement method for the major and minor axes conforms to the provisions of JIS Z8890:2017 "Evaluation of Particle Special Properties of Powders".
[0032] (B) The insulating layer formation step is a step of forming an insulating layer 8 having insulating properties on the surface of the rare earth magnetic powder 7 to obtain magnetic particles 6. The magnetic particles 6 are powder obtained by forming an insulating layer 8 on the rare earth magnetic powder 7. (B) In the insulating layer formation step, a nanoparticle dispersion liquid containing a plurality of fluoride nanoparticles 3A is sprayed onto the rolling flow device 20 of the rare earth magnetic powder 7 to form an insulating layer 8 on the surface of the rare earth magnetic powder 7. As described above, the fluoride nanoparticles 3A in this embodiment consist of calcium fluoride (CaF2) and are nanoparticles with a particle size of 1 to 100 nm.
[0033] The nanoparticle dispersion contains, for example, 4 wt% of fluoride nanoparticles 3A and 2.5 wt% of a binder compound. As a result, the insulating layer 8 formed by drying the nanoparticle dispersion contains 38 wt% of the binder compound and 62 wt% of fluoride nanoparticles 3A. The fluoride nanoparticles 3A are dispersed in the nanoparticle dispersion. The concentrations of fluoride nanoparticles 3A and the binder compound, as well as the solvent, in the nanoparticle dispersion may be changed.
[0034] The solvent for the nanoparticle dispersion is preferably 2-propanol (also known as "isopropyl alcohol" or "IPA"). The solvent for the binder compound solution does not have to be 2-propanol. The solvent for the binder compound solution is preferably an alcohol. To allow for easy evaporation after the rare earth magnetic powder 7 has been bonded in layers, the solvent for the binder compound solution is preferably a solvent that evaporates easily at room temperature.
[0035] Figure 4 is a schematic diagram of the rolling fluidizer 20. As shown in Figure 4, the rolling fluidizer 20 comprises a main body case 22 having a fluidized bed 21 inside for rolling and fluidizing rare earth magnetic powder 7, a rotatable blade rotor 23 defining the bottom of the fluidized bed 21, a spray nozzle 24 provided on the side of the main body case 22, and a blower (not shown) that sends a swirling flow of air into the fluidized bed 21 through the gap between the outer circumference of the blade rotor 23 and the main body case 22. The spray nozzle 24 is attached to the main body case 22 so that it can spray a binder compound solution toward the bottom of the fluidized bed 21.
[0036] (B) In the insulating layer formation process, as shown in Figure 4, rare earth magnetic powder 7 is placed in the fluidized bed 21 of the rolling fluidizer 20. The blade rotor 23 is rotated and a swirling flow of air in the fluidized bed 21 is generated by the blower. As a result, the rare earth magnetic powder 7 in the fluidized bed 21 rolls and flows. In this state, a nanoparticle dispersion is sprayed onto the rolling rare earth magnetic powder 7 from the spray nozzle 24. The sprayed nanoparticle dispersion adheres to the surface of the rare earth magnetic powder 7 and dries. As a result, an insulating layer 8 is formed on the surface of the rare earth magnetic powder 7, and magnetic particles 6 are obtained.
[0037] (C) The binder removal step is a step in which the magnetic particles 6 are heated to a temperature above the thermal decomposition temperature of the binder compound, causing the binder compound to decompose thermally and obtaining a degreased magnetic powder 11 from which the binder compound has been removed from the magnetic particles 6.
[0038] (C) In the binder removal process, the magnetic particles 6 may be heated in the mold of the hot press machine. As shown in Figure 3(C), the mold 30 of the hot press machine has a cylindrical mold body 31 and an upper mold 32 and a lower mold 33 that can apply a compressive force in a first direction to the object inside the mold body 31. In Figure 3, the first direction is the vertical direction, but the first direction may be a direction other than the vertical direction.
[0039] (C) In the binder removal process, the magnetic particles 6 placed in the mold body 31 of the mold 30 are heated to a temperature above the thermal decomposition temperature of the binder compound (e.g., 300°C to 400°C) for a predetermined time (e.g., 2 to 4 hours) in a reduced pressure environment or in an inert gas stream, without being pressurized by the mold 30 (upper mold 32 and lower mold 33). The inert gas is a gas that has poor reactivity with the rare earth magnetic powder 7. The inert gas is preferably a noble gas, for example. The inert gas is also preferably helium gas. Air may be used instead of the inert gas.
[0040] The products of the thermal decomposition of the binder compound are discharged from the mold 30. The binder compound is preferably an acrylic polymer (polymethyl methacrylate) with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer is thermally decomposed into the monomer methyl methacrylate. The decomposition products generated by the thermal decomposition of the binder compound volatilize and are discharged from the mold 30.
[0041] (C) When heating the magnetic particles 6 in a reduced-pressure environment during the binder removal process, the mold body 31 (mold 30) is heated in a reduced-pressure environment. When heating the magnetic particles 6 in an inert gas stream, the magnetic particles 6 are heated while an inert gas is flowed inside the mold body 31 (mold 30). The decomposition products of the binder compound (e.g., the monomer methyl methacrylate) become more volatile when placed in a reduced-pressure environment or in an inert gas stream, and are more easily discharged outside the mold body 31 (mold 30). In addition, the decomposition products of the binder compound are less likely to accumulate around the magnetic particles 6, and their reaction with the rare-earth magnetic powder 7, which degrades the rare-earth magnetic powder 7, is suppressed. It is preferable that the inert gas be heated to a temperature above the thermal decomposition temperature of the binder compound before being introduced into the mold 30. This promotes the thermal decomposition of the binder compound because the binder compound is heated by the inert gas.
[0042] (D) The primary molding process is a process in which the degreased magnetic powder 11 is primary molded using a hot press to obtain a primary molded body 12 in which the degreased magnetic powder 11 has been primary molded. (D) A mold 30 may be used in the primary molding process. (D) The primary molding process is also a process in which the degreased magnetic powder 11, from which the binder compound has been removed from the magnetic particles 6, is primary molded using a hot press to obtain a primary molded body 12.
[0043] (D) The primary molding step may be a step in which the degreased magnetic powder 11 is heated to a predetermined temperature in the mold 30 and a predetermined pressure is applied for a predetermined time to perform hot press molding (primary molding). Here, hot press molding may be performed at a mold temperature of 600°C to 700°C, preferably around 640°C. When the degreased magnetic powder 11 is pressurized in the mold 30, the multiple degreased magnetic powders 11 are oriented so that the main surface 7A of the rare earth magnetic powder 7 contained in the degreased magnetic powder 11 faces a first direction, and they are stacked on top of each other in a direction perpendicular to the main surface 7A (first direction). Therefore, by hot press molding, the multiple degreased magnetic powders 11 are compressed and deformed in a state where they are stacked on top of each other in a direction perpendicular to the main surface (main surface 7A of the rare earth magnetic powder 7) (first direction).
[0044] (E) The hot plastic deformation process is a process of obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 12 obtained in the (D) primary molding process. (E) In the hot plastic deformation process, the primary molded body 12 is heated and pressurized to a temperature at which some of the crystal grains of the rare earth magnetic powder 7 undergo a phase change to the liquid phase (the melting point of the rare earth magnetic powder 7, for example, around 850°C), thereby causing the primary molded body 12 to plastically deform.
[0045] (E) The hot plastic deformation process is performed using a secondary molding die 40. The secondary molding die 40 has an upper press mold 41 and a lower press mold 42 arranged opposite each other. The primary molded body 12 is placed in the secondary molding die 40 such that the multiple degreased magnetic powders 11 contained in the primary molded body 12 are pressed in a direction perpendicular to the main surface (first direction). During the plastic deformation process of the primary molded body 12, the c-axis direction (easy magnetization direction) of the crystal grains of the rare earth magnetic powder 7 contained in the primary molded body 12 is oriented parallel to the first direction (compression direction), so that magnetic anisotropy (uniaxial anisotropy) is exhibited in the primary molded body 12 during the plastic deformation process. The rare earth magnetic powder 2 contained in the rare earth magnet 1 is obtained when the rare earth magnetic powder 7 is plastically deformed and its crystal grains are oriented in the first direction (compression direction). The rare earth magnet 1 (see Figure 1) obtained in the hot composition processing process is magnetized in the direction in which this magnetic anisotropy is exhibited (first direction).
[0046] (E) In the hot plastic working process, the degreased magnetic powder 11 is heated while being pressurized in a direction perpendicular to the main surface of the degreased magnetic powder 11 (first direction). As a result, the crystal grains in the magnet are shorter in the first direction (compression direction) and longer in the orthogonal direction perpendicular to the first direction (direction in which the main surface extends). Furthermore, after the (E) hot plastic working process, the rare earth magnet 1 is magnetized in the first direction (compression direction). Due to the orientation of the crystal grains of the rare earth magnet 1 as described above and the magnetization as described above, the square ratio of the rare earth magnet 1 is close to 1.
[0047] Furthermore, as shown in Figure 1, the rare earth magnet 1 is an aggregate of rare earth magnet powder 2 having an insulating layer 3 on its surface, and the insulating layer 3 increases its electrical resistivity. As a result, the overcurrent loss of the rare earth magnet 1 is reduced. Therefore, the rare earth magnet 1 has a suitable square aspect ratio and reduced overcurrent loss.
[0048] Next, the effects of the rare earth magnet 1 manufactured in this manner and its manufacturing method will be explained.
[0049] The rare earth magnetic powder 7 is flaky and has a particle size of 500 μm to 600 μm. Figure 5 is a graph showing the difference in residual magnetic flux density and coercivity between a rare earth magnet 1 manufactured from the rare earth magnetic powder 7 of the example, which is flaky and has a particle size of 500 μm to 600 μm, and a rare earth magnet manufactured from the rare earth magnetic powder of the comparative example, which is flaky and has a particle size of 1 μm to 600 μm.
[0050] The oxygen concentration of the rare earth magnet 1 in the example was 0.11 wt%, while the oxygen concentration of the rare earth magnet in the comparative example was 0.16 wt%. Therefore, the rare earth magnet 1 in the example had a lower oxygen concentration than the rare earth magnet in the comparative example. As shown in Figure 5, the rare earth magnet 1 in the example had improved residual magnetic flux density (Figure 5(A)) and improved coercivity (Figure 5(B)) compared to the rare earth magnet in the comparative example. This is thought to be because the rare earth magnetic powder 7 is in the form of flakes with a particle size of 500 μm to 600 μm, which is larger than that of typical rare earth magnetic powders.
[0051] The rare earth magnetic powder 7 has a relatively larger particle size than commonly used rare earth magnetic powders, resulting in a smaller specific surface area. As a result, the rare earth magnetic powder 7 is less susceptible to oxidation during the manufacturing process of the rare earth magnet 1, thus reducing the oxygen concentration of the rare earth magnet 1 produced from the rare earth magnetic powder 7. This improves the magnetic properties of the rare earth magnet 1 produced from the rare earth magnetic powder 7. Here, magnetic properties refer to, for example, the remanent magnetic flux density (see Figure 5(A)) and coercivity (see Figure 5(B)). Therefore, it is possible to provide a rare earth magnetic powder 7 that can serve as a material for a rare earth magnet 1 with good magnetic properties.
[0052] As shown in Figure 2, the magnetic particles 6 consist of flaky rare earth magnetic powder 7 and an insulating layer 8 formed on the surface of the rare earth magnetic powder 7, with the particle size of the rare earth magnetic powder 7 being between 500 μm and 600 μm.
[0053] As a result, the rare earth magnetic powder 7 contained in the magnetic particles 6 has a larger particle size than the rare earth magnetic powder commonly used to manufacture rare earth magnets, resulting in a smaller specific surface area of the rare earth magnetic powder 7. This makes the rare earth magnetic powder 7 less susceptible to oxidation during the manufacturing process of the rare earth magnet 1, and also reduces the volume ratio of the insulating layer 8 in the rare earth magnet 1. Because the rare earth magnetic powder 7 is less susceptible to oxidation and the volume ratio of the insulating layer 8 in the rare earth magnet 1 is reduced, the magnetic properties (e.g., residual magnetic flux density) of the rare earth magnet 1 are improved. Therefore, it is possible to provide magnetic particles 6 that can serve as a material for a rare earth magnet 1 with good magnetic properties.
[0054] A method for manufacturing a rare earth magnet 1 includes (B) an insulating layer formation step to obtain magnetic particles 6 by forming an insulating layer 8 on the surface of flake-shaped rare earth magnetic powder 7 with a particle size of 500 μm or more and 600 μm or less; (D) a primary molding step to obtain a primary molded body 12 by primary molding the magnetic particles 6 obtained in step (B) using a hot press; and (E) a hot plastic deformation step to obtain a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 12. This makes it possible to manufacture a rare earth magnet 1 with good magnetic properties.
[0055] In the manufacturing method of the rare earth magnet 1, the oxygen concentration of the rare earth magnetic powder 7 is adjusted so that the rare earth magnet 1 obtained in the (E) hot plastic working step contains 0.12 wt% or less of oxygen. As a result, the oxygen concentration of the rare earth magnet 1 is relatively low, making it possible to manufacture a rare earth magnet 1 with good magnetic properties.
[0056] The manufacturing method for the rare earth magnet 1 involves (B) forming an insulating layer 8 with a thickness of 200 nm to 2 μm in the insulating layer formation step. This forms an insulating layer 3 that can appropriately increase the electrical resistivity of the rare earth magnet 1, thereby enabling the manufacture of a rare earth magnet 1 with reduced overcurrent loss.
[0057] This concludes the description of specific embodiments, but the present invention is not limited to the above embodiments and can be broadly modified and implemented. For example, the solvent for the binder compound solution and the nanoparticle dispersion does not have to be IPA, but may be an alcohol that is liquid at room temperature, such as 1-propanol or butanol.
[0058] The above embodiments may also be described as follows:
[0059] One embodiment is a rare earth magnetic powder 7, which is in the form of flakes and has a particle size of 500 μm or more and 600 μm or less.
[0060] According to this embodiment, the rare earth magnetic powder 7 has a larger particle size than the rare earth magnetic powder commonly used to manufacture rare earth magnets, and therefore has a smaller specific surface area. As a result, the rare earth magnetic powder 7 is less likely to oxidize during the manufacturing process of the rare earth magnet 1, thereby improving the magnetic properties of the rare earth magnet 1 manufactured from the rare earth magnetic powder 7. Therefore, it is possible to provide a rare earth magnetic powder 7 that can be used as a material for a rare earth magnet 1 with good magnetic properties.
[0061] In one embodiment, the magnetic particles 6 that are the material for the rare earth magnet 1 include flaky rare earth magnetic powder 7 and an insulating layer 8 having insulating properties formed on the surface of the rare earth magnetic powder 7, wherein the particle size of the rare earth magnetic powder 7 is 500 μm or more and 600 μm or less.
[0062] According to this embodiment, the rare earth magnetic powder 7 has a larger particle size than the rare earth magnetic powder commonly used to manufacture rare earth magnets, resulting in a smaller specific surface area. This makes the rare earth magnetic powder 7 less susceptible to oxidation during the manufacturing process of the rare earth magnet 1, and also reduces the volume ratio of the insulating layer 8 in the rare earth magnet 1. By making the rare earth magnetic powder 7 less susceptible to oxidation and reducing the volume ratio of the insulating layer 8 in the rare earth magnet 1, the magnetic properties of the rare earth magnet 1 can be improved. Therefore, it is possible to provide magnetic particles 6 that can serve as material for a rare earth magnet 1 with good magnetic properties.
[0063] In one embodiment, a method for manufacturing a rare earth magnet 1 includes: (B) an insulating layer formation step to obtain magnetic particles 6 by forming an insulating layer 8 on the surface of flake-shaped rare earth magnetic powder 7 with a particle size of 500 μm or more and 600 μm or less; (D) a primary molding step to obtain a primary molded body 12 in which a plurality of magnetic particles 6 obtained in step (B) are primary molded using a hot press; and (E) a hot plastic deformation step to obtain a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 12 obtained in step (D).
[0064] According to this embodiment, a rare-earth magnet 1 with good magnetic properties can be manufactured.
[0065] In one embodiment, the method for manufacturing the rare earth magnet 1 is such that the oxygen concentration of the rare earth magnetic powder 7 is adjusted so that the rare earth magnet 1 obtained in the (E) hot plastic deformation step contains 0.12 wt% or less of oxygen.
[0066] According to this embodiment, a rare earth magnet 1 with a relatively low oxygen concentration can be manufactured, and therefore, a rare earth magnet 1 with good magnetic properties can be manufactured.
[0067] In one embodiment, the method for manufacturing the rare earth magnet 1 involves (B) forming an insulating layer 8 with a thickness of 200 nm or more and 2 μm or less in the insulating layer formation step.
[0068] According to this embodiment, since the insulating layer 8 is formed in such a way that the electrical resistivity of the rare earth magnet 1 can be appropriately increased, it is possible to manufacture a rare earth magnet 1 with reduced overcurrent loss. [Explanation of Symbols]
[0069] 1: Rare earth magnets 3: Insulating layer 6:Magnetic particles 7: Rare earth magnetic powder 8: Insulating layer 12: Primary molded body
Claims
1. Rare earth magnetic powder, which is a material for rare earth magnets, Rare earth magnetic powder having a flaky appearance and a particle size of 500 μm to 600 μm.
2. Magnetic particles that are materials for rare earth magnets, Scale-like rare earth magnetic powder, The rare earth magnetic powder has an insulating layer formed on its surface, Magnetic particles having a particle size of 500 μm or more and 600 μm or less of the rare earth magnetic powder.
3. A method for manufacturing rare earth magnets, An insulating layer formation step to obtain magnetic particles by forming an insulating layer on the surface of a flake-shaped rare earth magnetic powder with a particle size of 500 μm or more and 600 μm or less, A primary molding step involves primary molding the plurality of magnetic particles obtained in the insulating layer forming step using a hot press to obtain a primary molded body in which the plurality of magnetic particles are primary molded, A method for manufacturing a rare earth magnet, comprising: a hot plastic deformation step of performing hot plastic deformation on the primary molded body obtained in the primary molding step to obtain a rare earth magnet.
4. The method for manufacturing a rare earth magnet according to claim 3, wherein the oxygen concentration of the rare earth magnetic powder is adjusted so that the rare earth magnet obtained in the hot plastic deformation step contains 0.12 wt% or less of oxygen.
5. The method for manufacturing a rare earth magnet according to claim 3, wherein in the insulating layer formation step, the insulating layer having a thickness of 200 nm or more and 2 μm or less is formed.
Citation Information
Patent Citations
High resistance rare earth magnet and its manufacturing method
JP2003022905A
Method of manufacturing r-t-b based rare earth magnet
JP2010027852A
Rare earth magnet and method for manufacturing the same
JP4784173B2